HUBUNGAN PENGETAHUAN DAN PERSEPSI REMAJA PUTRI DENGAN PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI DI SMP IT ZAINAL ABIDIN KOTA LANGSA - Dira Qinaya; Yusria Yusria; Ina Rahawa (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: Menstruation is a normal physiological process that occurs in adolescent girls. However, poor personal hygiene practices during menstruation can lead to various health problems such as vaginal discharge, urinary tract infections, and reproductive tract infections. Personal hygiene behavior during menstruation is strongly influenced by the level of knowledge and perception that adolescents have about the importance of maintaining personal cleanliness. Poor menstrual hygiene behavior increases the risk of reproductive health disorders among adolescent girls. Objective: This study aims to determine the relationship between the level of knowledge and perception of adolescent girls with their personal hygiene behavior during menstruation at SMP IT Zainal Abidin, Langsa City. Method: This research used a quantitative analytic method with a descriptive correlational design and a cross-sectional approach. The population consisted of 46 female students who had experienced menstruation, with the sampling technique being total sampling. The research instrument used questionnaires on knowledge, perception, and personal hygiene behavior, which had been tested for validity and reliability. Data were analyzed using univariate and bivariate analysis with the Chi-Square test at a significance level of α = 0.05. Results: The results showed that most respondents had a moderate level of knowledge (56.5%), all respondents had a positive perception (100%), and the majority had poor personal hygiene behavior (84.8%) during menstruation. The Chi-Square test results showed no significant relationship between knowledge and personal hygiene behavior (p = 0.556) and no significant relationship between perception and personal hygiene behavior (p = 0.884). Conclusion: Good knowledge and perception do not necessarily lead to good personal hygiene behavior during menstruation. Other factors such as habits, hygiene facilities, and environmental support play important roles in shaping healthy personal hygiene behavior among adolescent girls.